Estimation of upper air relative humidity For objective analysis - KULKARNR, P. L.; SINHA, S. K.; TALWALKAR, D. R.; NARKHEDKAR, S.G.; NAIR , S.; RAJAMANI, S. (MAUSAM, 1991)
A multiple regression relation was developed between upper air relative humidity and the related surface observations, like cloud cover, present weather and surface relative humidity etc. Using this regression relation at a number of surface observing stations the relative humidity values for upper air at 700 hPa west estimated from surface relative humidity, cloud cover and present weather for six days from 4 to 9 July 1979. In order to determine the impact of these estimated value, two sets of analyses were made using optimum interpolation scheme, one including estimated RH values and the second excluding them RMS errors were calculated for all the SIX cases, comparing with the observed radiosonde data to examine how both sets of analyses with and without estimated data fitted the observations. RMS errors were also computed comparing with ECMWF-RH Analyses. Lastly, these analyst's were compared with satellite cloud pictures and found them in close agreement with the observed data.